The Association Between the Pattern of Electronic Cigarette Smoking and Gastroesophageal Reflux - Ahmad Fariz Malvi Zamzam Zein; Donny Nauphar; Uswatun Khasanah; Tiar M Pratamawati; Rama S Brajawikalpa; Eka Ayuningtyas; Alif Hamzah (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy, 2021)
Background: This study was aimed to investigate the proportion of gastroesophageal reflux (GER) among electronic cigarette (e-cig) smokers and its association with the pattern of e-cig smoking.